THE NOSTALGIA VALUE OF VIRAL RESTAURANTS: THE IMPORTANCE OF HUMAN ATMOSPHERE AND PERCEIVED VALUE ON INTENTION TO RETURN - Ruspitasari, Widi Dewi (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
Culinary tourism in East Java is growing quite rapidly. The purpose of this study is to determine how important nostalgia marketing influences the intention to revisit viral restaurants in East Java. and what aspects can influence consumers to visit the viral wizzmie restaurant in East Java. To test this relationship, researchers used 100 respondents who had visited the viral wizzmie restaurant using PLS analysis. The PLS model shows that nostalgia does not have a direct impact on the intention to revisit consumers, but is influenced by other factors, namely perceived value and human atmosphere.